Peningkatan Ipteks Masyarakat Pulau Kabung dalam Pengendalian Hama Melalui Pelatihan Aplikasi Perangkap Warna Berperekat Atraktan dari Tumbuhan Aromatik Lokal: Pengabdian - Dwi Isyana Achmad; Okto Ivansyah; Muhammad Rizal; Muflihah Ramadhia; Tika Rahma Yunita; Muliani; Narsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This community service (PPM) program was conducted on Kabung Island, Karimunting Village, Sungai Raya Kepulauan District, Bengkayang Regency, West Kalimantan. The partners involved were community groups representing the northern, southern, western, and eastern parts of Kabung Island. The partners were vegetable and plantation crop farmers who experienced difficulties in controlling pests on their crops. This PPM activity aimed to provide partners with additional knowledge and skills in pest control using local natural resources. The program consisted of several stages: coordination, outreach, technical training, and activity evaluation. 100% of participants experienced increased knowledge and skills in making and applying pest traps. Furthermore, increased productivity and crop quality were observed several months after using the pest traps. Based on these results, it can be analyzed whether partner income will increase if the pest trap application is implemented sustainably in crop cultivation on Kabung Island.